Evaluation of inhibitory activities of two medicinal plant extracts Parkia biglobosa and Lonicera japonica against spoilage microorganisms isolated from mulberry fruit. Issue 8 (10th June 2020) - Herman, Richard A.; Wang, Jin‐Zheng; Amuzu, Prosper; Shittu, Saidi; Wu, Fu‐An; Wang, Jun
Abstract: Two medicinal plants, African Locust Bean ( Parkia biglobosa ) and Lonicera japonica, traditionally used in West Africa and China were investigated against four spoilage microorganisms: Bacillus subtilis, Cronobacter dublinensis, Pantoea agglomerans, and Bacillus sp ., isolated from mulberry fruit. The aqueous extract of the P. biglobosa (ALB) was potent with average inhibitory zones against four spoilage microorganisms recorded as (Means ± SD ) 6.5 to 19.5 mm as well as 6.5 to 15.5 mm for L. japonica (HSF) at concentrations of 400 mg/ml. The aqueous extracts of P. biglobosa (54%) inhibited decay better than L. japonica (66%). Decay situations of the medicinal plants with 1‐MCP emerged higher than the control group 78%, 72%, and 68% in ALB + 1‐MCP, HSF + 1‐MCP, and deionized water, respectively. Therefore, two plant extracts against spoilage microorganisms isolated from mulberry fruit had good inhibitory activities, but their mixture with 1‐MCP could not preserve the mulberry fruits in limited storage time. Practical applications: Advance in the bacteria control using a natural control like medicinal plants against plant infections was investigated. The present study demonstrated the potentials of African locust bean and L. japonica as a novel biocontrol agent to the extent of preserving the postharvest decay of mulberry fruit in limited storage time at room temperature. The results and findings obtained in this study support the potential application of these two plants in mulberry fruit preservation as well as in traditional therapeutics. In addition, the combination with 1‐MCP also serves as the potential to extend the shelf life of mulberry fruit in order to limit the use of pesticides in postharvest treatments. This study reports for the first time isolated microorganisms from mulberry fruit and the developments of edible coatings utilizing plant extracts from different continents against their activities.